2014
DOI: 10.1155/2014/514036
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Flammability Factors of Kenaf and Allied Fibre Reinforced Polymer Composites

Abstract: Natural fibre is a well-known reinforcement fibre in polymer-matrix Composites (PMC) lately. Natural fibre has fast growing and abundance properties which make it available at very low cost. For kenaf fibre there is long lists of research projects which have been done regarding its behaviour, and properties and modification made to it. In this paper, fire flammability is the main concern for natural fibre reinforced polymer (NFRP) composites especially kenaf fibre. To estimate its flammability, a wide range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The kenaf plant can grow to about 1.5 m in 120 days and its stem is made of bark and core fibers. The plant's core resembles wood and makes up 60-70% of the stem's dry weight; bark fibers contribute to the remaining 30-40%, and have a dense structure [9]. Several studies have reported the use of kenaf core fibers (KCF) as reinforcements in composite panels [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The kenaf plant can grow to about 1.5 m in 120 days and its stem is made of bark and core fibers. The plant's core resembles wood and makes up 60-70% of the stem's dry weight; bark fibers contribute to the remaining 30-40%, and have a dense structure [9]. Several studies have reported the use of kenaf core fibers (KCF) as reinforcements in composite panels [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It was created for the greener, safer and better performance of the biopolymer. A lower manufacturing energy is required to produce FLO since it can be processed at about 160 °C, while most of the matrices require a temperature higher than 180 °C (Shukor et al 2014 ; Ersoy and Taşdemir 2012 ; Liang et al 2011 ; Libolon 2015 ; Lee et al 2014 ). Besides this, it ensures a lower chance of fibre thermal degradation, especially for a low thermal stability natural fibre.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that some conventional products (such as natural fiber reinforced polymer composite) do not adequately fulfill safety and fire resistance requirements (Lee et al 2014), especially in the aerospace, automotive, electronics, building-construction, and biotechnology industries. Hence, the awareness about these materials performance and their response during fire allows the incorporation of fire retardant materials in polymeric materials for development of products for different applications.…”
Section: Introductionmentioning
confidence: 99%